1981
DOI: 10.1111/j.1600-0773.1981.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Methyl Mercury with Monoamine Uptake and Release in Rat Brain Synaptosomes

Abstract: Interference of methyl mercury (Met-Hg), a known neurotoxin, with the high affinity uptake and the release of tritiated dopamine (DA), noradrenaline (NA) and serotonin (5-HT) was studied in vitro in rat stnatal, cortical and hypothalamic synaptosomes respectively. Met-Hg proved to be a potent inhibitor of uptake; the IC50's were 2.5 pM (DA), 3.2 pM (NA) and 3.4 pM (5-HT) in 2min. incubations. The uptake of NA was slightly inhibited already at 0.1-1 pM Met-Hg whereas DA and 5-HT were not. The inhibition was rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Both MeHg and PCBs may also affect the central monoaminergic system as well. In fact, altered dopaminergic neurotransmission has been observed following perinatal exposure to MeHg (0.5 mg/kg/day, GD7-PND7) in rats [ 53 , 54 ]; moreover, MeHg can stimulate the spontaneous release of monoamines from different experimental CNS tissue preparations [ 55 , 56 ]. The most consistent neurochemical effects of noncoplanar PCBs have been found to be a reduction in dopamine (DA) concentrations besides an increase in DA concentration both in cells and striatal tissue cultures [ 57 – 59 ] as well as in laboratory animals brains after developmental or adult exposure (for a review, [ 18 ]), with an exacerbation of the effects of the two contaminants acting synergistically when coadministrated [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both MeHg and PCBs may also affect the central monoaminergic system as well. In fact, altered dopaminergic neurotransmission has been observed following perinatal exposure to MeHg (0.5 mg/kg/day, GD7-PND7) in rats [ 53 , 54 ]; moreover, MeHg can stimulate the spontaneous release of monoamines from different experimental CNS tissue preparations [ 55 , 56 ]. The most consistent neurochemical effects of noncoplanar PCBs have been found to be a reduction in dopamine (DA) concentrations besides an increase in DA concentration both in cells and striatal tissue cultures [ 57 – 59 ] as well as in laboratory animals brains after developmental or adult exposure (for a review, [ 18 ]), with an exacerbation of the effects of the two contaminants acting synergistically when coadministrated [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two such studies reporting no association 9 , 10 , while a larger-scale study of 6911 samples reporting a negative association (i.e., greater blood mercury levels correlated with lower odds of depression) in older adults (the same tendency is seen in young adults as well) 8 . In addition, animal studies have reported an association between greater methylmercury levels in the brain and inhibition of monoamine uptake 37 or monoamine oxidase 38 , both of which are supposed to have anti-depressant effects 39 . Therefore, one speculation is that although high-level mercury exposure can cause neurodegeneration, leading to cognitive dysfunction and depression, lower-level daily exposure (albeit relatively high in Japan) has anti-depressant effects mediated by effects on monoamine systems.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in our previous study 35 , whole-brain analyses tend to overestimate effect sizes, especially in small samples, due to over-fitting. 35 Thus, individual small sample studies tend to have greater effect sizes than meta-analyses 37 . In the current study, several hundred individual datasets were included in each analysis but the observed effects sizes were relatively small (|partial correlation coefficients|< 0.18).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MeHg towards the adrenergic system have been less investigated than the dopaminergic system. Early in vitro studies reported that MeHg caused inhibition of norepinephrine uptake and stimulated its release from pre-loaded synaptosomes (Komulainen and Tuomisto, 1981;Rajanna and Hobson, 1985) and hippocampal slices (Gassó et al, 2000). The effects of perinatal in vivo exposure to MeHg have consistently indicated changes in brain norepinephrine levels in rats.…”
Section: Epinephrinementioning
confidence: 99%